Sturge-Weber syndrome: Case report, literature review and proposed pregnancy care plan. (December 2022) - Byrne, Bridgette; O'Carroll, Robert ffrench; Doherty, Colin
The pregnancy of a 38-year-old woman with Sturge-Weber syndrome and epilepsy is described here, with safe outcome for mother and baby despite considerable controversy about peripartum care. Literature review reveals seven case reports of pregnancy in women with Sturge-Weber syndrome and there is little to guide clinicians in the management of these complex cases. A care pathway for women with Sturge-Weber syndrome that are planning pregnancy or are pregnant is proposed.